2022
DOI: 10.3390/microorganisms11010075
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton Community Response to Environmental Factors along a Salinity Gradient in a Seagoing River, Tianjin, China

Abstract: A river-estuary ecosystem usually features a distinct salinity gradient and a complex water environment, so it is enormously valuable to study the response mechanism of living organisms to multiple abiotic factors under salinity stress. Phytoplankton, as an important part of aquatic microorganisms, has always been of concern for its crucial place in the aquatic ecosystem. In this study, phytoplankton data and 18 abiotic factors collected from 15 stations in Duliujian River, a seagoing river, were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 70 publications
(116 reference statements)
1
14
0
Order By: Relevance
“…The river’s proximity to the ocean renders it susceptible to saltwater intrusion. Consequently, the entire river exhibits a salinity gradient that, in conjunction with other abiotic conditions, influences the survival, growth, and reproduction of aquatic creatures [ 10 ]. Please refer to [ 10 ] for the specific study area and sampling station, and the map is depicted in the Supplementary Materials for the convenience of reviewers and readers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The river’s proximity to the ocean renders it susceptible to saltwater intrusion. Consequently, the entire river exhibits a salinity gradient that, in conjunction with other abiotic conditions, influences the survival, growth, and reproduction of aquatic creatures [ 10 ]. Please refer to [ 10 ] for the specific study area and sampling station, and the map is depicted in the Supplementary Materials for the convenience of reviewers and readers.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the environmental factors had significant seasonal variations, and the distributions of important environmental factors are shown in the Supplementary Materials (Table S2 and Figure S2) . For detailed descriptions of the environmental factors, please refer to the previous article [ 10 ], which was about the effects of environmental factors on the phytoplankton community. Since the sampling time of the zooplankton data in this paper was exactly the same as that of the phytoplankton data in the previous paper, the descriptions of the environmental factors are not described again in this paper in order to avoid duplication.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies on phytoplankton communities have demonstrated that phytoplankton-community characteristics such as species richness, community diversity, and community evenness can be driven by many abiotic factors and biological factors [Sun et al, 2023]. Studies have proven that phytoplankton community, species richness, community diversity, and species abundance are all closely related to nutrient concentrations [Soininen and Meier, 2014; Lusiana et al, 2020].…”
Section: Factors Affecting Phytoplankton Community In the Two Pondsmentioning
confidence: 99%